Determinants of financial condition in Malaysia - Yee, Ling Pang; Lee, Hock Ann (European Publisher, 2020)
This research studies the determinants of financial condition in Malaysia. It employs the external financial variables from the United States (U.S.) and domestic financial variables from Malaysia. The research assesses the long-run association among the domestic and external indicators via the ARDL bounds test approach and monthly time series data starting from January 2008 to May 2018. This research also investigates the level of the effect caused by the U.S. financial variables on the financial condition in Malaysia. The empirical findings have proven the validity of the long-run association between the majority of domestic financial indicators with the asset side of the U.S. balance sheet (lnUSTA) and the Fed funds rate (USFUND). Particularly, lnUSTA has appeared as a key determinant to the financial condition in Malaysia, specifically the Kuala Lumpur Composite Index, Malaysian credit spread, Malaysian overnight policy rate, and Malaysian term spread which has the highest level of negative effect at 1.412%. In contrast, USFUND does not show significant long-run influence with the involved domestic financial indicators except with the Malaysian credit spread.